2018
DOI: 10.1101/362525
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of the Ghrelin/Growth Hormone Secretagogue Receptor System in the Human Heart Before and After Cardiac Transplantation

Abstract: we examined tissue ghrelin-GHSR levels as specific markers of cardiac dysfunction in patients 8 who underwent cardiac transplantation. 9 Methods and Results 10

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…GHSR expression in healthy, developing, and diseased heart models, as well as human hearts. 78,79 The increasing promise of fluorescently labeled ghrelin analogues contributed to a desire to develop ghrelin imaging probes with improved metabolic stability. Recently, ghrelin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) was cyclized through a lactam bridge between Glu 12 and Lys 16 for improved stability of secondary structure, and labeled with the SulfoCy5 dye off the C-terminal lysine residue (Figure 5).…”
Section: Molecular Imaging Agents Based On Ghrelinmentioning
confidence: 99%
“…GHSR expression in healthy, developing, and diseased heart models, as well as human hearts. 78,79 The increasing promise of fluorescently labeled ghrelin analogues contributed to a desire to develop ghrelin imaging probes with improved metabolic stability. Recently, ghrelin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) was cyclized through a lactam bridge between Glu 12 and Lys 16 for improved stability of secondary structure, and labeled with the SulfoCy5 dye off the C-terminal lysine residue (Figure 5).…”
Section: Molecular Imaging Agents Based On Ghrelinmentioning
confidence: 99%
“…Ghrelin actions are mediated via activation of the G protein coupled receptor (GPCR) growth hormone secretagogue receptor type 1a (GHS‐R1a) . It was originally reported that GHS‐R1a was found within the pituitary gland and hypothalamus, but recent work has revealed a more widespread expression in other tissues, including the brain and heart . GHS‐R1a is also reported to be differentially expressed in certain cancer cells.…”
Section: Figurementioning
confidence: 99%